The Breakfast Habits Related with Nutritional Status of Students in State Madrasah Ibtidaiyah 1 Kuantan Singingi - Rici Syahrani; Nur Pelita Sembiring; Sofya Maya (Journal of Applied Food and Nutrition, 2023)
Fulfillment of nutritional needs in the morning can be obtained from breakfast, there was by fulfilling 15-30% of daily nutrient intake. Currently, there are still many Indonesian children who still need to consume breakfast under balanced nutrition recommendations. Children who rarely had breakfast are at risk of nutrient deficiencies, affecting their nutritional status. The study aimed to determine the correlation of breakfast habits to the nutritional status of students in State Madrasah Ibtidaiyah (MIN) 1 Kuantan Singingi. This research was conducted in MIN 1 Kuantan Singingi on February 2023. This research method used a cross-sectional design and a total sampling technique. Variabels in this research included breakfast obtained by breakfast recall questionnaire interviews and nutritional status determined based on measurements of the z-socre of BMI/Age. The results showed that 47,5% respondents were normal category and about 57.5% respondents had good breakfast habits. Based on the Chi-Square test results obtained a value of p=0.7460.05, it can be concluded that there was no significant correlation between breakfast to the nutritional status of students in MIN 1 Kuantan Singingi.